1995
DOI: 10.1021/np50118a008
|View full text |Cite
|
Sign up to set email alerts
|

Venezenin: A New Bioactive Annonaceous Acetogenin from the Bark of Xylopia aromatica

Abstract: Asimicin and a new cytotoxic Annonaceous acetogenin, venezenin [1], were isolated from the bark of Xylopia aromatica by bioactivity-directed fractionation using lethality to brine shrimp. Compound 1 represents an unusual type of C37 Annonaceous acetogenin, lacking either tetrahydrofuran (THF) or epoxide rings and possessing a double bond located two methylenes away from a vicinal diol in the hydrocarbon chain. The structure of 1 was elucidated by 1H- and 13C-nmr, COSY, single-relayed COSY, and by HMBC techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 12 publications
1
31
0
1
Order By: Relevance
“…Alkaloids, amides, lignoids, acetogenines and terpenes (mono, di and sesquiterpenes) are the most important metabolites (Martins et al, 1999;Stashenko et al, 2004). Because stems are especially rich in acetogenines (Saizarbitoria et al, 1994(Saizarbitoria et al, , 1995Alfonso et al, 1996), this metabolite could be responsible for antiparasitic activity observed in this study.…”
Section: Discussionmentioning
confidence: 64%
“…Alkaloids, amides, lignoids, acetogenines and terpenes (mono, di and sesquiterpenes) are the most important metabolites (Martins et al, 1999;Stashenko et al, 2004). Because stems are especially rich in acetogenines (Saizarbitoria et al, 1994(Saizarbitoria et al, , 1995Alfonso et al, 1996), this metabolite could be responsible for antiparasitic activity observed in this study.…”
Section: Discussionmentioning
confidence: 64%
“…The same comment can be made for goniothalamicin and its translactonized derivative goniothalamicinone. It is interesting that reference of a tetrahydrofuran ring is not essential, since venezenin shows promising activity (30).…”
Section: )mentioning
confidence: 99%
“…Várias espécies da família Annonaceae foram estudadas empregando o bioensaio TAS, juntamente com outros ensaios biológicos [7][8][9][10] . Porém, nenhuma espécie do gênero Unonopsis havia sido quimicamente investigada utilizando monitoramento por bioensaio.…”
Section: Introductionunclassified